KONSEP PUBLIC GOODS DAN FLOW CONCEPT DALAM UANG MENURUT EKONOMI ISLAM - susila, susila; Rafi’i, Muhammad; Suci, Mirna; Raya, Bella Cinu; Mumtazah, Nada Luqyana (Universitas Muhammadiyah Surabaya, 2022)
Islam views money as a medium of exchange, not as a commodity. Widespread awareness of the role of money aims to eliminate injustice and injustice in the exchange economy. they are classified as fadl riba. Exchange is an unrealistic method of exchange and proves the unimportance of the overall market mechanism. Literature study is data deepening based on theoretical studies and scientific work references. descriptive qualitative research. Data collection techniques in literature study, namely the collection of literature related to research, then analysis and conclusions about public goods, namely the general public can use it without disturbing the use by other people or certain parties. The money saved is not used for the manufacturing sector (idle assets). This amount is reduced because of the obligation of zakat on Muslims. So the money must be rotated (the concept of cash flow). Should not be productive and used as a transaction tool. Like the spirit of Fastabigul Hoyrot, Islam encourages competition in the economic field. alms, waqf, and other activities. The money must also be used for investments and contracts such as musyarokah, mudharabah, wadiah, qardh, and others, in the real sector, as exemplified by the Prophet Muhammad.